Ecoturismo em áreas protegidas: efetividade da gestão do uso público em unidades de conservação na região de Diamantina-MG - Ezio Dornela Goulart (2014)
Ecotourism, which can be considered a new and broad issue, has received a variety of interpretations, in a diverse context of practices and concepts, but still in need of conclusions that mean changes in socio-environmental activities to which it proposes. This study aims to analyze the ecotourism activity as an effective tool for the sustainable development and biodiversity conservation, in protected natural areas in Diamantina, Brazil. For that, there was an assessment of the current situation of the management of public use activities, focusing on the visit to three State Parks, analyzing the profile of the conservation areas, pressures and threats, opportunities, vulnerabilities and management effectiveness. The methodology involved the researchers participation in the public use activities in the protected areas, the development and use of a questionnaire to diagnose, assess the context and public use management as well as the interpretation of the collected information together with the managers of such areas. The research covered the State Parks of Rio Preto, Pico do Itambé and Biribiri, protected areas which have legal authorization for activities related to visiting, that is, programs and/or public use plans. For the development of the data collecting tool, the methodology of RAPPAM (Rapid Assessment and Prioritization of Protected Area Management ) was employed and adapted for the management analysis of programs/ public use plans. The outcomes showed that the effectiveness of the public use management ranged from medium to high and the most critical factor was the forest fires. It was also verified that the biggest vulnerability relies on the difficulty in hiring human resources and the parameter with the worst evaluations is related to research, assessment and monitoring of the public use activities. It was observed that factors such as landing legalization and infrastructure implementation may have influenced the results of public use management. So, the collected information subsidized the analysis of questions which cover the ecotourism management, its reproduction and organization in protected natural areas. In conclusion, the developed ecotourism activity in the parks has neither provided the desired economical resources nor involved the local communities effectively. On the other hand, the developed ecotourism is close to the concept when the environmental knowledge dimension and the educational interpretive experience are analyzed.